Home My Page Projects Code Snippets Project Openings diderot

SCM Repository

[diderot] View of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml
 [diderot] / branches / charisee_dev / src / compiler / high-il / normalize-ein.sml

View of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml

Tue Oct 8 19:42:58 2013 UTC (5 years, 11 months ago) by cchiw
Original Path: branches/charisee/src/compiler/high-il/normalize-ein.sml
File size: 18244 byte(s)
`working in einTest so won'te compile`
```structure NormalizeEin = struct

local

structure E = Ein
structure P=Printer
structure O =OrderEin
in

(*Flattens Add constructor: change, expression *)
|flatten(i,((E.Const c):: l'))=
if (c>0.0 orelse c<0.0) then let
val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end
else flatten(1,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let
val(b,a)=flatten(i,l') in (b,[e]@a) end

val (b,a)=flatten(0,e)
in case a
of [] => (1,E.Const(1.0))
| [e] => (1,e)
(* end case *)
end

fun mkProd [e]=(1,e)
| mkProd(e)=let
fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')
|flatten(i,((E.Const c)::l'))=
if(c>0.0 orelse  0.0>c) then (3,[E.Const 0.0])
else flatten(i,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let val(a,b)=flatten(i,l') in (a,[e]@b) end
val (change,a)=flatten(0,e)
in if(change=3) then (1,E.Const(0.0))
else case a
of [] => (1,E.Const(0.0))
| [e] => (1,e)
| es => (change, E.Prod es)
(* end case *)
end

(*

fun mkEps(e)= (case e
of E.Apply(E.Partial [E.V a], E.Prod( e2::m ))=> (0,e)
| E.Apply(E.Partial [E.V a,E.V b], E.Prod( (E.Epsilon(i,j,k))::m ))=>
(if(a=i andalso b=j) then (1,E.Const(0.0))
else if(a=i andalso b=k) then (1,E.Const(0.0))
else if(a=j andalso b=i) then (1,E.Const(0.0))
else if(a=j andalso b=k) then (1,E.Const(0.0))
else if(a=k andalso b=j) then (1,E.Const(0.0))
else if(a=k andalso b=i) then (1,E.Const(0.0))
else (0,e))
|_=> (0,e)
(*end case*))

fun mkSumApply(E.Sum(c,E.Apply(d, e))) = (case e
of E.Tensor(a,[])=> (0,E.Const(0.0))
| E.Tensor _=> (0,E.Sum(c,E.Apply(d,e)))
| E.Field _ =>(0, E.Sum(c, E.Apply(d,e)))
| E.Const _=> (1,E.Const(0.0))
| E.Sub(e2, e3) =>(1, E.Sub(E.Sum(c,E.Apply(d, e2)), E.Sum(c,E.Apply(d, e3))))
| E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))
| E.Prod[E.Tensor(a,[]), e2]=>  (1, E.Prod[ E.Tensor(a,[]), E.Sum(c,E.Apply(d, e2))]  )
| E.Prod((E.Tensor(a,[]))::e2)=>  (1, E.Prod[E.Tensor(a,[]), E.Sum(c,E.Apply(d, E.Prod e2))] )
| E.Prod es =>   (let
fun prod [e] = (E.Apply(d, e))
| prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]
val lr=e2 @[E.Apply(d,e1)]   val(b,a) =mkProd lr
in ( E.Add[ a, m] ) end)
| prod _= (E.Const(1.0))
in (1, E.Sum(c,prod es))  end)
| _=> (0,E.Sum(c,E.Apply(d,e)))
(*end case*))

*)

fun rmEpsIndex(_,_,[])=[]
| rmEpsIndex([],[],cs)=cs
| rmEpsIndex([],m ,e1::cs)=[e1]@rmEpsIndex(m,[],cs)
| rmEpsIndex(i::ix,rest ,(E.V c)::cs)=
if(i=c) then rmEpsIndex(rest@ix,[],cs)
else rmEpsIndex(ix,rest@[i],(E.V c)::cs)

(* Transform eps to deltas*)
fun epsToDels(E.Sum(count,E.Prod e))= let
fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=
let

(*Function is called when eps are being changed to deltas*)
fun createDeltas(i,s,t,u,v, e3)= let

(*remove index from original index list*)
(*currrent, left, sumIndex*)

val s'= rmEpsIndex([i,s,t,u,v],[],count)
val s''=[E.V s, E.V t ,E.V u, E.V v]
val deltas= E.Sub(
E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),
E.Sum(s'',E.Prod([E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]@e3)))

in (case (eps,s')
of ([],[]) =>(1,deltas)
|([],_)=>(1,E.Sum(s',deltas))
|(_,[])=>(1,E.Prod(eps@[deltas]))
|(_,_) =>(1, E.Sum(s', E.Prod(eps@[deltas])))
)
end

in if(a=d) then createDeltas(a,b,c,e,f, e3)
else if(a=e) then createDeltas(a,b,c,f,d, e3)
else if(a=f) then createDeltas(a,b,c,d,e, e3)
else if(b=d) then createDeltas(b,c,a,e,f, e3)
else if(b=e) then createDeltas(b,c,a,f,d,e3)
else if(b=f) then createDeltas(b,c,a,d,e,e3)
else if(c=d) then createDeltas(c,a,b,e,f,e3)
else if(c=e) then createDeltas(c,a,b,f,d,e3)
else if(c=f) then createDeltas(c,a,b,d,e,e3)
else (0,E.Const 0.0)
end
fun findeps(e,[])= (e,[])
| findeps(e,(E.Epsilon eps)::es)=  findeps(e@[E.Epsilon eps],es)
| findeps(e,es)= (e, es)

fun dist([],eps,rest)=(0,eps,rest)
| dist([e],eps,rest)=(0,eps@[e],rest)
| dist(c1::current,eps,rest)=let
val(i, exp)= doubleEps(c1::current,eps,rest)
in  (case i of 1=>(i,[exp],[E.Const 2.0])
|_=> dist(current, eps@[c1],rest))
end

val (es,rest)=findeps([],e)

in
dist(es,[],rest)
end

fun rmIndex(_,_,[])=[]
| rmIndex([],[],cs)=cs
| rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)
| rmIndex(i::ix,rest ,c::cs)=
if(i=c) then rmIndex(rest@ix,[],cs)
else rmIndex(ix,rest@[i],c::cs)

(* Apply deltas to tensors/fields*)
fun reduceDelta(E.Sum(c,E.Prod p))=let

fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)
| findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)
| findDeltas(dels,rest,es)=  (dels,rest,es)

fun distribute(change,d,dels,[],done)=(change,dels@d,done)
| distribute(change,[],[],e,done)=(change,[],done@e)
| distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)
| distribute(change,E.Delta(i,j)::ds,dels,E.Field(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)
| distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])

val (dels,eps,es)=findDeltas([],[],p)
val (change,dels',done)=distribute([],dels,[],es,[])
val index=rmIndex(change,[],c)

in
(change, E.Sum(index,E.Prod (eps@dels'@done)))
end

fun mkApplySum(E.Apply(E.Partial d,E.Sum(c,e)))=(print "apply sum";case e
of E.Tensor(a,[])=>(1,E.Const 0.0)
| E.Const _ =>(1,E.Const 0.0)
| E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, E.Sum(c,e))) l))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, E.Sum(c,e2)), E.Apply(E.Partial d, E.Sum(c,e3))))

| E.Prod [e1]=>(1,E.Apply(E.Partial d,E.Sum(c,e1)))
| E.Prod(E.Tensor(a,[])::e1::[])=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Sum(c,e1))])

| E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Sum(c,E.Prod e2))])
(*  | E.Prod es=> (let
fun prod [e1] =E.Apply(E.Partial d,e1)
| prod(e1::e2)=(let
val l= prod(e2) val m= E.Prod[e1,l]
val lr=e2 @[E.Apply(E.Partial d,e1)] val(b,a) =mkProd lr
end)
in (1,prod es) end)*)
|_=>(0,E.Apply(E.Partial d,E.Sum(c,e)))
(* end case*))

fun mkApply2(E.Apply(E.Partial d,e))=(print "aa";case e
of E.Tensor(a,[])=>(1,E.Const 0.0)
| E.Const _ =>(1,E.Const 0.0)
| E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, e)) l))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, e2), E.Apply(E.Partial d, e3)))
| E.Apply(E.Partial e1,e2)=>(1,E.Apply(E.Partial(d@e1), e2))
| E.Prod [e1]=>(1,E.Apply(E.Partial d,e1))
| E.Prod(E.Tensor(a,[])::e1::[])=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,e1)])
| E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Prod e2)])
| E.Prod es=> (let
fun prod [e1] =(0,E.Apply(E.Partial d,e1))

| prod(E.Tensor t::e2)=(let
val (change,l)= prod(e2) val m= E.Prod[E.Tensor t,l]
val lr=e2 @[E.Apply(E.Partial d,E.Tensor t)] val(b,a) =mkProd lr
end)
| prod(E.Field f::e2)=(let
val (change,l)= prod(e2) val m= E.Prod[E.Field f,l]
val lr=e2 @[E.Apply(E.Partial d,E.Field f)] val(b,a) =mkProd lr
end)
| prod e = (0,E.Apply(E.Partial d, E.Prod e))
(*)prod (e1::e2)= E.Apply(E.Partial d, E.Prod ([e1]@e2))
*)

val (a,b)= prod es

in (a, b) end)
|_=>(0,E.Apply(E.Partial d,e))
(* end case*))

fun mkSumApply2(E.Sum(c,E.Apply(E.Partial d,e)))=(print "in here ";case e
of E.Const _=>(1,E.Const 0.0)
| E.Tensor(_,[])=> (1,E.Const 0.0)
| E.Field _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))
| E.Apply(E.Partial e1,e2)=>(1,E.Sum(c,E.Apply(E.Partial(d@e1),e2)))

| E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))
| E.Sub(e2, e3) =>
(*(0,E.Sub(e2,e3))
*)
(print "sub";(1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e2)), E.Sum(c,E.Apply(E.Partial d, e3)))))

| E.Prod [e1]=>(print "one";(1,E.Sum(c,E.Apply(E.Partial d,e1))))

| E.Prod(E.Tensor(a,[])::e2::[])=>("in scalar";(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,e2))]))

| E.Prod(E.Tensor(a,[])::e2)=>("in scalar";(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))]))

| E.Prod es =>(print "in prod";let
fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))
| prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let
fun matchprod(2,_,_,_)= 1 (*matched 2*)
| matchprod(num,_,_,[])=0
| matchprod(0,_,_,[eps])=0
| matchprod(num,[],rest,eps::epsx)=
matchprod(num,rest,[],epsx)
| matchprod(num,E.V p::px,rest,eps::epsx)=
if(p=eps) then matchprod(num+1,px,rest,epsx)
else matchprod(num,px,rest@[E.V p], eps::epsx)
| matchprod(num,p::px,rest,eps)=
matchprod(num,px,rest,eps)

val change'= matchprod(0,d,[],[i,j,k])
in (case change'
of 1 => (1,E.Const 0.0)
| _ =>prod(change,rest@[E.Epsilon(i,j,k)],sum,partial,ps)
(*end case*))
end
| prod (change,rest, sum,partial,E.Delta(i,j)::ps)=let
fun applyDelPartial([],_)=(0,[])
| applyDelPartial(p::px,r)=
if(j=p) then (1,r@[i]@px)
else  applyDelPartial(px,r@[p])

val (change',px)=applyDelPartial(d,[])

in (case change'
of 1 => (let val index=rmIndex([j],[],sum)
in prod(1,rest, index,px, ps) end )
| _ => prod(change,rest@[E.Delta(i,j)], sum,partial, ps)
(*end case*)) end

| prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)

val (change,exp) = prod(0,[],c, d, es)

in
(change,exp)
end)
| _=>(print "nope";(0,E.Sum(c,E.Apply(E.Partial d,e))))
(* end case*))

(*
E.Sum(c,Apply(d,e))
try E.Sum(c,e)=> E.Sum(c',e')
==>    E.Sum(c',E.Apply(d,e'))
E.Apply(d,e')=> E.Apply(d',e'')
==>E.Sum(c',E.Apply(d',e'')
*)

(*Apply normalize to each term in product list
or Apply normalize to tail of each list*)
fun normalize (Ein.EIN{params, index, body}) = let

val changed = ref false

fun rewriteBody body = (case body
of E.Const _=> body
| E.Tensor _ =>body
| E.Field _=> body
| E.Kernel _ =>body
| E.Delta _ => body
| E.Value _ =>body
| E.Epsilon _=>body

| E.Neg e => E.Neg(rewriteBody e)
in if (change=1) then ( changed:=true;body') else body' end
| E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)
| E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)
| E.Partial _=>body
| E.Conv (V, alpha)=> E.Conv(rewriteBody V, alpha)
| E.Probe(u,v)=>  E.Probe(rewriteBody u, rewriteBody v)
| E.Image es => E.Image(List.map rewriteBody es)

(*Product*)
| E.Prod [e1] => rewriteBody e1
(changed := true; E.Add(List.map (fn e=> E.Prod([e1, e]@e3)) e2))
| E.Prod(e1::(E.Sub(e2,e3))::e4)=>
(changed :=true; E.Sub(E.Prod([e1, e2]@e4), E.Prod([e1,e3]@e4 )))
| E.Prod [E.Partial r1,E.Conv(f,deltas)]=>
(changed:=true;E.Conv(f,deltas@r1))
| E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>
(changed:=true;
let val (change,e)=mkProd([E.Conv(f,deltas@r1)]@ps)
in e end)
| E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>
if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))
else body
| E.Prod [E.Partial r1, E.Tensor(_,[])]=> (changed:=true;E.Const(0.0))
| E.Prod(E.Partial r1::E.Partial r2::p)=>
(changed:=true;E.Prod([E.Partial(r1@r2)]@p))
| E.Prod [E.Partial _, _] =>body

| E.Prod (E.Partial p1::es)=> (let
fun prod [e1] =E.Apply(E.Partial p1,e1)
| prod(e1::e2)=(let
val l= prod(e2) val m= E.Prod[e1,l]
val lr=e2 @[E.Apply(E.Partial p1,e1)] val(b,a) =mkProd lr
end)
in (changed:=true;prod es) end)

| E.Prod(e::es)=>let
val e'=rewriteBody e
val e2=rewriteBody(E.Prod es)
val(a,b)=(case e2 of E.Prod p'=> mkProd([e']@p')
|_=>mkProd [e',e2])
in b
end

(*Apply*)

| E.Apply(E.Partial d,E.Sum(c,e))=>let
val(c,e')=mkApplySum(E.Apply(E.Partial d,E.Sum(c, rewriteBody e)))
in (case c of 1=>(changed:=true;e')
|_=> e')end
| E.Apply(E.Partial [],e)=> e

| E.Apply(E.Partial p, e)=>let
val body'=E.Apply(E.Partial p, rewriteBody e)
val (c, e')=mkApply2(body')
in (case c of 1=>(changed:=true;e')
| _ =>e') end
| E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)

(* Sum *)
| E.Sum([],e)=> (changed:=true;rewriteBody e)
| E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
| E.Sum(c,E.Sub(e1,e2))=>(changed:=true; E.Sub(E.Sum(c,e1),E.Sum(c,e2)))
| E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>
let val (i,e,rest)=epsToDels(body)
in (case (i, e,rest)
of (1,[e1],_) =>(changed:=true;e1)
|(0,eps,[])=>body
|(0,eps,rest)=>(let
val p'=rewriteBody(E.Prod rest)
val p''= (case p' of E.Prod p=>p |e=>[e])
val(a,b)= mkProd (eps@p'')
in E.Sum(c,b) end
)
|_=>body)
end
| E.Sum(c, E.Prod(E.Delta d::es))=>let
val (change,a)=reduceDelta(body)
val (change',body')=(case a
of E.Prod p=> mkProd p
|_=> (0,a))
in (case change of []=>body'|_=>(changed:=true;body')) end

| E.Sum(c,E.Apply(E.Partial _,e))=>let
val (change,exp)=mkSumApply2(body)
val exp'=(case exp
of  E.Const c => E.Const c
| E.Sum(c',E.Apply(d',e'))  => (let
val s'=rewriteBody(E.Sum(c',e'))
in (case s'
of E.Sum([],e'')=>E.Apply(d',e'')
| E.Sum(s'',e'') => E.Sum(s'',E.Apply(d',e''))
| _ => E.Apply(d',s'))

end)

| _ =>exp
(* end case *))

in (case change of 1=>(changed:=true;exp') |_=>exp')
end

| E.Sum(c,e)=>E.Sum(c,rewriteBody e)

(*end case*))

fun loop body = let
val body' = rewriteBody body
in
if !changed
then (changed := false; print " \n \t => \n \t ";print( P.printbody body');print "\n";loop body')
else (P.printbody(body');body')
end
val b = loop body
in
((Ein.EIN{params=params, index=index, body=b}))
end
end

end (* local *)```